ANALISIS TERHADAP JANGKA WAKTU PERJANJIAN KERJA WAKTU TERTENTU MENURUT UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN (STUDI KASUS: PUTUSAN PENGADILAN PENYELESAIAN HUBUNGAN INDUSTRIAL PADA PENGADILAN NEGERI JAKARTA PUSAT NOMOR 133 /Pdt.Sus-PHI.G/2016/ PN.JKT.PST) - Aurelia Giani; Andari Yurikosari (Fakultas Hukum Universitas Tarumanagara, 2018)
109 people have worked at PT. Cantik Aura. they have worked for 3 (three) to 24 (twenty four) years. but their employment status is still a fix term of labor contract. whereas according to Law Number 13 of 2003 on Manpower it for the sake of law turned into a working agreement uncertain time. This 109 people filed a lawsuit but the court's decision rejected all claims of these 109 plaintiffs. on the basis of judges' consideration of the types and properties of the work of the plaintiffs is temporary. whereas their working period has passed based on Law Number 13 of 2003 on Manpower. Based on the type and nature of employment for a specified period of employment arranged by Law Number 13 Year 2003 on Manpower, the work done by the workers is not included in Article 59 Paragraph (1) that is, once completed or temporary work, which is expected to be completed within a period of not more than 3 (three) years, seasonal work or work relating to new products, new activities or additional products that are still under trial or exploration. In its legal considerations, the Supreme Court of Justice in the case only considers that the type of work of the workers is temporary and does not take into consideration that the type of work that is said while it is being perpetrated continuously, does not stop and the passage of the term of the particular employment agreement. The law itself imposes restrictions on the term of a specific employment agreement to protect workers from corporate deviations.